Android-Based Smart Tourism Application Design In Dangiang Cibeger Natural Tourism, Garut Regency - Sopiyan, Deni (Jurnal Computech & Bisnis (e-journal), 2025)
Dangiang Cibeger Nature Tourism, situated in Samida Village, Garut Regency, boasts significant natural and cultural assets, encompassing educational bamboo tourism, rice planting tourism, plowing tourism, fish farming tourism, homestays, villas, camping grounds, glamping, swimming pool tourism, and outbound activities.  Nonetheless, these resources remain suboptimally utilized.  To improve competitiveness and the quality of tourism services, extensive planning and design are essential through the use of a Smart Tourism application.  This project seeks to provide a design for a Smart Tourism application for Dangiang Cibeger Nature Tourism in Garut Regency.  The application design incorporates several key features, including tourism village information, virtual tours, a reservation system, online payment options, electronic tickets, navigation systems, and augmented reality experiences.  The deployment of the Smart Tourism application is expected to enhance operational efficiency, improve tourist experiences, and empower local communities through technology.